Un peruanista francés en los Andes: entrevista a Pierre Duviols - Itier, César; Guibovich Pérez, Pedro (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
In this interview, Pierre Duviols, one of the most renowned French Peruvianists, speaks about his biographical and scholarly trajectory. He presents a detailed picture of his family environment, his studies, the origins of his interest in the history of the Andes, and his relationships with Peruvian scholars since his arrival in Peru in the mid-20th century. He also tells us of his perspectives on research and his work methodology.

En esta entrevista, Pierre Duviols, uno de los más destacados peruanistas franceses, nos habla de su trayectoria biográfica y académica. Expone en detalle acerca de su entorno familiar, sus estudios, los orígenes de su vocación por el estudio de la historia de los Andes y las relaciones que mantuvo con los estudiosos peruanos desde su llegada al Perú a mediados del siglo XX. Además, nos informa de sus perspectivas de estudio y su metodología de trabajo.
A French Peruvianist in the Andes: An interview with Pierre Duviols
Keywords: Duviols; Historia Andina; Historiografia; Historia Colonial; Metodología; https://purl.org/pe-repo/ocde/ford#6.01.01